2019
DOI: 10.1002/cctc.201901682
|View full text |Cite
|
Sign up to set email alerts
|

A Minireview on Nickel‐Based Heterogeneous Electrocatalysts for Water Splitting

Abstract: developing non-precious electrocatalysts with high performance is of primary significance in a fascinating and scalable water splitting technology for hydrogen production. A number of nickel (Ni)-based heterogeneous catalysts have been designed and synthesized to lower the overpotentials for large current densities due to low cost and facile synthesis. Herein, recent progress on Ni-based composites functioning on hydro-gen evolution reaction (HER), oxygen evolution reaction (OER), and overall water splitting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 137 publications
(54 reference statements)
0
44
0
Order By: Relevance
“…[11][12][13] In particular, Ni-oxide nanomaterials are well-assessed Earth abundant materials for efficient OER, especially in combination with other metal dopants. 4,5,11,[14][15][16] NiO-based nanostructures have already shown very proficient catalytic actions in sensing, electrochromical smart windows, supercapacitors and energy applications. [17][18][19][20][21][22][23] Such materials have great potential to work also as an efficient backboneplatform electrocatalyst for both the HER and the OER.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] In particular, Ni-oxide nanomaterials are well-assessed Earth abundant materials for efficient OER, especially in combination with other metal dopants. 4,5,11,[14][15][16] NiO-based nanostructures have already shown very proficient catalytic actions in sensing, electrochromical smart windows, supercapacitors and energy applications. [17][18][19][20][21][22][23] Such materials have great potential to work also as an efficient backboneplatform electrocatalyst for both the HER and the OER.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Ni-based nanostructures are thus extremely appealing as a full water splitting cell can be realized with bi-functional heterogeneous electrocatalytic sites for the HER and the OER. 16 It has been recently shown that Ni-Co-Fe sulphide nanosheets on Ni nanocones act as high performance electrocatalysts for total electrochemical water splitting at a potential of 1.54 V to give a current density of 10 mA cm À2 . 28 Similarly, Fe 2+ -doped layered double (Ni, Fe) hydroxides are used for overall water splitting showing an overpotential of 1.54 V to give a current density of 10 mA cm À2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,45] As the OÀ O bond formation is not the ratedetermining step, it is difficult to establish from the kinetics if this nickel catalyst follows the mononuclear water nucleophilic attack or the dinuclear radical oxo coupling mechanism. [19,23] The order in 1 was determined by performing water oxidation at different complex concentrations. Figure 6b shows that the data can be linearly fitted if we plot the oxygen evolution rate versus the square root of the catalyst concentration.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] In proton-exchange membrane (PEM) cells, iridium is often used as catalyst at the anode, while in alkaline electrolyzers the catalyst is typically based on nickel. [3,23,24] Inspired by photosystem II in nature, [25][26][27][28] a significant amount of research has been devoted to develop molecular WOCs. These systems have the advantage of being easier to study, as well as being more active per metal center.…”
Section: Introductionmentioning
confidence: 99%